Synthesis of copper-containing metal–polymer nanocomposites and their use as a humidity sensor - Igor E. Uflyand; Vladimir A. Zhinzhilo; Tatjana V. Lifintseva (ChemPhysMater)
Recently, the synthesis of new gas-sensitive materials for use in resistive humidity sensors has attracted considerable interest. In the study, copper-containing metal–polymer nanocomposites were obtained by thermolysis of copper fumarate (I) and its complexes with 2,2′-dipyridyl (II) and 1,10-phenanthroline (III). The nanocomposites were characterized by Fourier transform infrared (FTIR) spectroscopy, elemental analysis, energy-dispersive X-ray (EDX) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The most common particle sizes of the thermolysis products of compounds I, II, and III were 18.7, 8.3, and 20.7 nm, respectively. The manufactured sensor samples exhibited good sensitivity to the relative humidity (RH) of air: 2.48%/%RH, 3.77%/%RH, and 3.11%/%RH for the thermolysis products of compounds I, II, and III, respectively. Because of the high porosity and moisture absorption of the film, the maximum sensitivity was approximately 0.005 MΩ/%RH, which indicates fairly effective behavior of the film with respect to humidity. The response and recovery times were 23.7, and 37.3 s; 24.7, and 35.8 s; 32.4, and 58.4 s, respectively. The experiment had 88%–97% reproducibility. The fabricated sensors have great potential as humidity-sensing elements for humidity monitoring.